(untitled) (Journal of Medical Sciences, 2025)
In dental practice, it is common to see patients who have one or more teeth that are developmentally absent. Significant functional, cosmetic, and psychosocial issues are linked to tooth agenesis. Dental agenesis is a crucial problem that has not received enough attention in Libyan research. Because the management calls for a multidisciplinary approach, it is significant from an academic and clinical standpoint to shed some light on this anomaly. There has been a recent emphasis on the need to identify research gaps in this sector and support the scientific community by conducting studies on the genetic origins of tooth agenesis and tumor development. The occurrence and characteristics involved in tooth agenesis in Sirte orthodontic patients are summarized in this article. Appropriate planning and management may be difficult, and patient care will probably necessitate multidisciplinary and interdisciplinary involvement. However, prompt diagnosis can help. Dental professionals must possess a thorough understanding of tooth agenesis’s clinical features and available treatments. Non-syndromic tooth agenesis has been occasionally described in literature and data available for its prevalence is rare in Libya. This retrospective radiography study’s objective was to gather information on the frequency and pattern of non-syndromic congenital teeth missing in orthodontic patients. The data for this study were chosen from 500 consecutive orthodontic patients who matched the inclusion criteria. The radiographic data had at least one orthopantomogram (OPG) of clear, sufficient quality, which was complemented with periapical radiographs as needed. From statistical analysis a prevalence of 3.8 percent hypodontia was seen in the sample. It was determined that the frequency of hypodontia in the Sirte orthodontic population of Libya is 3.8%, which is within the range globally. However, to precisely estimate the prevalence of hypodontia, more research needs be done on a larger non-orthodontic population. The current study’s objective was to establish baseline data by determining the characteristics of congenital absence of the permanent teeth in Sirte, Libya.